By His Excellency Benning Wentworth, Esq ; captain-general, governor and commander in chief in and over his Majesty's province of New-Hampshire ... A proclamation for a general thanksgiving : His Majesty having been pleased to signify his royal pleasure, that a public thanksgiving, should be observed in his American colonies, on the happy conclusion of the peace. ... Thursday, the eleventh of August, shall be observed and kept as a day of publick thanksgiving ... Given at the Council-chamber in Portsmouth, the 28th day of July, in the third year of His Majesty's reign, 1763 ([Printed by D. Fowle], 1763)
July 28, 1763 Proclamation by Governor Benning Wentworth establishing August 11th as a day of general thanksgiving for the conclusion of peace with the Treaty of Paris.